Islamic Religious Education As A Form - Nadia Nadia; Arrohman Arrohman (Proceeding International Seminar of Islamic Studies, 2019)
Islamic education is a whole human education, Mind and Heart, His spiritual and temporal, and her skills. Here Islamic education is a process of individual formation based on the teachings of Islam revealed by Allah SWT, More emphasis on Islamic education meaning